Arithmetic and Geometry Around Quantization - Ceyhan, Özgür; Manin, Yu. I.; Marcolli, Matilde (Progress in Mathematics,, 2010)
In recent decades, quantization has led to interesting applications in various mathematical branches. This volume, comprised of research and survey articles, discusses key topics, including symplectic and algebraic geometry, representation theory, quantum groups, the geometric Langlands program, quantum ergodicity, and non-commutative geometry. A wide range of topics related to quantization are covered, giving a glimpse of the broad subject. The articles are written by distinguished mathematicians in the field and reflect subsequent developments following the Arithmetic and Geometry around Quantization conference held in Istanbul. List of Contributors: S. Akbulut R. Hadani S. Arkhipov K. Kremnizer Ö. Ceyhan S. Mahanta E. Frenkel S. Salur K. Fukaya G. Ben Simon D. Gaitsgory W. van Suijlekom S. Gurevich.